The Effectiveness of School-Based Disaster Management Education on Knowledge and Preparedness of D-III Nursing Study Program Students - Hermansyah Hermansyah; Muhammad Muhammad; Nurhayati Nurhayati; Masyudi Masyudi (Postgraduate, University of Mataram, 2023)
Various disasters have occurred due to lack of knowledge and unpreparedness of the community in the pre-disaster phase. In fact, preparedness has not become a permanent behavior in society so that if a disaster occurs, it is predicted that they will not take care themselves and others. Nursing students as prospective nursing staff must be equipped with knowledge, attitudes and practices in dealing with disasters. This quantitative research aims to determine the effectiveness of the school-based disaster management education model on the knowledge and preparedness of nursing students. A quasi-experimental method is used in the form of a one group pretest-posttest design on 80 Diploma III Nursing students who were trained by facilitators for 6 months. Data were collected using questionnaires and observations, then analyzed using the Paired t-test and Multiple Linear Regression (95% CI; Î±=0.05). The results showed that disaster management education model can increase knowledge (p=0.000) and preparedness (p=0.002) in facing disasters. Disaster preparedness is significantly related in predicting disaster knowledge scores (r=0.708). If a disaster occurs, nursing students are able to help themselves and the disaster victims. This model can also be used as an evaluation of learning outcomes for the Disaster Nursing course